Icarrin prevents cardiomyocyte apoptosis in spontaneously hypertensive rats by inhibiting endoplasmic reticulum stress pathways. (21st May 2021) - Qian, Zhiqiang; Zhu, Ling; Li, Yeli; Li, Yiqi; Wu, Yuting; Fu, Shu; Yang, Danli
Abstract: Objectives: This study aimed to explore whether icarrin (ICA) can protect cardiomyocytes from hypertension-induced damage by inhibiting endoplasmic reticulum stress (ERS). Methods: Spontaneously hypertensive rats (SHRs) were orally administered water or ICA at 10, 20 and 40 mg/kg once daily for 12 weeks, and Wistar–Kyoto (WKY) rats were used as control. Changes in the growth and blood pressure of rats were assessed. Cardiac function was determined by ultrasound and the left ventricle mass was calculated. Myocardial tissue structure was assessed by haematoxylin and eosin staining, cardiomyocyte apoptosis was observed by TUNEL staining and the expression of ERS-related proteins was determined by western blotting. Results: In the SHR group, blood pressure was significantly high, left ventricular function decreased and left ventricular mass index increased. Additionally, left ventricular cardiomyocyte hypertrophy, disordered myofilament arrangement and increased cardiomyocyte apoptosis were observed by histological staining. ERS-induced proteins associated with apoptosis, including GRP78, PERK, ATF-6, ATF-4, CHOP, DR5, Caspase 12, c-JUN and ASK-1 were found to be highly expressed. ICA treatment reduced blood pressure and regulated the expression of proteins induced by ERS. Cardiomyocyte apoptosis decreased and left ventricular function improved. Conclusions: ICA can inhibit ERS-induced apoptosis of cardiomyocytes and protect ventricular function in SHR.